PHILOSOPHY OF THE PROFESSION IN THE STRUCTURE OF SCHOOLTEACHER PROFESSIONAL IDENTITY IN LATVIAN AND RUSSIAN SAMPLES - Jermolajeva, Jelena; Bogdanova, Tatiana; Silchenkova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents the results of the international study of the professional identity (PI) of schoolteachers of Russia and Latvia. The six component model of the content of the PI is used in the study. According to this model, the questionnaire “School Teacher Professional Identity” was created and international survey organized in 2017, in which 433 schoolteachers from Latvia and the Smolensk region of Russia participated. The aim of this article is to analyze the data of two national samples for the first component of the schoolteacher PI: Philosophy of the Profession. The data in both samples show very high support for the basic values and beliefs of the profession. The answers of the teachers of the two countries are well agreed, however certain differences in the data of Latvian and Russian teachers are observed. Some problems of the schoolteacher PI are identified that require attention of teachers, school administrators and education officials.